Implementasi penggunaan e-book pendidikan kewarganegaraan terhadap kemandirian belajar mahasiswa: pendekatan student-centered learning - Dian Nastiti (Didaktika Dwija Indria, 2025)
Abstract.Civic Education plays a pivotal role in shaping individuals who are politically literate, ethical, and socially responsible. This course aims to equip students with the knowledge, skills, and attitudes necessary for active and constructive participation in national and civic life. However, one of the main factors contributing to the low level of student engagement in Civic Education courses is the use of less effective learning models during instruction. The implementation of a Civic Education E-Book as a flexible and interactive medium, framed by a Student-Centered Learning (SCL) approach that fosters independent exploration, is not merely modernization but a strategic necessity. In the current era of technological and informational disruption, innovation in learning media and resources has become imperative. The transition from printed textbooks to electronic books (e-books) is an inevitable development in higher education. This study employed a descriptive qualitative approach. The results indicate that the implementation of the Civic Education E-Book has had a positive impact on enhancing students’ learning autonomy through the SCL approach. The use of e-books not only facilitates easier access to learning resources but also transforms the interaction pattern between lecturers and students. Students become more active in independently exploring, comprehending, and interpreting learning materials, reducing their reliance on lecturers’ explanations.